ВДОСКОНАЛЕННЯ АДМІНІСТРАТИВНОГО ЗАКОНОДАВСТВА, ЯКЕ РЕГЛАМЕНТУЄ ДІЯЛЬНІСТЬ АПАРАТУ СУДУ В УКРАЇНІ - Макаровець, Алла Миколаївна (SUPREMANCE OF LAW, 2018)
The article substantiates the significance of the improvement of administrative legislation, which regulates the activity of the court apparatus in Ukraine. There is the analysis of its current state the main drawbacks are revealed. The ways of improvement of the administrative legislation, which regulates the activity of the court apparatus in Ukraine, are offered.
Keywords: court; court apparatus; position; head of the court; assistant judge; administrative law